Esterification of Palmitic Acid with Methanol in the Presence of Macroporous Ion Exchange Resin as Catalyst - Yaakob, Amellia Qarina; Bhatia, Subhash (IIUM Press, International Islamic University Malaysia, 2004)
The esterification of palmitic acid with methanol was studied in a batch reactor using macro porous ion exchange resin Amberlyst 15 as a catalyst. Methyl palmitate was produced from the reaction between palmitic acid and methanol in the presence of catalyst. The effects of processing parameters, molar ratio of alcohol to acid M, (4-10), catalyst loading (0-10 g cat/liter), water inhibition (0-2 mol/liter), agitator speed (200- 800 rpm) and reaction temperature (343-373K) were studied. The experimental kinetic data were correlated using homogenous as well as heterogeneous models (based on single as well as dual site mechanisms). The activation energy of the reaction was 11.552 kJ/mol for forward reaction whilst 5.464 kJ/mol for backward reaction. The experimental data fitted well with the simulated data obtained from the kinetic models.